Web based heritage food selling system / Zulkifli Awang - Awang, Zulkifli (2013)
Nowadays, the emergence of personalization application for online shopping in business industries is the new approach to help business gain most benefits for their companies. E-Commerce, with the Internet as its main platform has a very large market network. The research has contributed online shopping for the Heritage Foods. Heritage Foods Selling System has brought the new ideas to expend the heritage foods coverage. Heritage Foods Selling System contributed the ideas in integrating the online shopping and hoping that all customers around Kelantan can purchase the heritage foods easily. The system provides facilities for customers to place orders, and purchases a recommend products based on customer needs electronically. The system developed in the Windows environment using Macromedia Dreamweaver MX 2004 as the scripting language. MySQL and Wamp Server are used as the database management system. During the development process, the Waterfall Model is implemented where it acts as a methodology in developing the system. From evaluation the respondents many agreed that the system user interface and usability is acceptable and easy to use. The development of such system is expected to be the driver for the growth of product sales and market.